GAMBARAN KESEHATAN MENTAL MAHASISWA TINGKAT AKHIR PRODI SARJANA KEPERAWATAN ITEKES BALI PADA MASA PANDEMI COVID-19 - Ni Komang Sri Cahyani; Ni Luh Adi Satriani; Putu Noviana Sagitarini (Coping: Community of Publishing in Nursing, 2021)
Background: Corona virus disease 2019 is a disease that attacks the respiratory tract. In order to break the chain of transmission of this disease, the government takes a policy by implementing massive restriction (PSBB) which requires all activities to be carried out at home including lectures such as writing thesis for final year students. The impact of these policies can affect the mental health of final year students. Aim: To describe the mental health of final year students of Bachelor of Nursing Program at ITEKES Bali during the Covid-19 pandemic. Methods: This study employed a quantitative descriptive design with a cross-sectional approach. The study was conducted at Institute of Technology and Health (ITEKES) Bali on February-March 2021. There were 161 respondents recruited as the sample through saturated with non-probability sampling technique. Data were collected by using Self Reporting Questionnaire which was modified by the researcher based on a literature review and has been tested for validity. Finding: The finding indicated that there were 92 respondents (57.1%) had mental health problems.Conclusion: It is hoped that students can apply mental health care and further researchers can look for the influence of the role of parents in maintaining students' mental health when facing thesis preparation during the Covid-19 pandemic.